A comparison of the outcomes of four minimally invasive treatment methods for anterior disc displacement of the temporomandibular joint. Issue 11 (November 2017) - Hosgor, H.; Bas, B.; Celenk, C.
Abstract: The purpose of this study was to compare the effectiveness of four non-surgical conservative treatment methods for temporomandibular disorders (TMD). The study group comprised 40 patients with unilateral TMD who fell into group II of the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD). Patients were divided into four groups according to the treatment method: splint therapy, arthrocentesis, medical therapy, and low-level laser therapy. Magnetic resonance imaging (MRI) was performed before treatment and at the 1-month follow-up. The type of TMD and joint effusion were examined in the MRI scans. Patients were followed up after treatment for 6 months. Mouth opening increased and pain scores decreased at 1, 3, and 6 months after treatment in all groups ( P < 0.05). No statistically significant difference in the improvements in clinical symptoms was observed between the groups. A positive correlation was found between pain and effusion ( P < 0.05). A significant positive relationship was also found between internal derangement and effusion ( P < 0.05). All treatment methods were successful at improving the clinical symptoms. It was determined that the effusion demonstrated on MRI was associated with pain. Although the symptoms improved after treatment, joint effusion did not show any decrease in the 1-month follow-up MRI.